2017
DOI: 10.1002/fuce.201600165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Ammonia‐fueled Solid Oxide Fuel Cell Systems

Abstract: Several solid oxide fuel cell (SOFC) systems can be considered for the NH3 utilization. In this study, the catalytic activity and long‐term stability of the NH3 decomposition reactor with the Ni/Y2O3‐based catalysts and the autothermal NH3 cracker with the Co–Ce–Zr composite oxide catalyst were investigated. Moreover, the NH3 decomposition reactor and the autothermal NH3 cracker were combined with the SOFC stack and their performances of the stack were compared to those fueled with NH3 and H2/N2. The power out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 85 publications
(46 citation statements)
references
References 43 publications
0
30
1
2
Order By: Relevance
“…In our previous report, the supported catalyst of SrO‐Ni/Y 2 O 3 for ammonia decomposition was developed and investigated . It was found that the strong basic property of SrO as an additive enhanced ammonia decomposition , and almost 100% ammonia was decomposed into hydrogen and nitrogen at 650 °C at a space velocity (SV) of 2,400 h −1 .…”
Section: Methodsmentioning
confidence: 92%
See 3 more Smart Citations
“…In our previous report, the supported catalyst of SrO‐Ni/Y 2 O 3 for ammonia decomposition was developed and investigated . It was found that the strong basic property of SrO as an additive enhanced ammonia decomposition , and almost 100% ammonia was decomposed into hydrogen and nitrogen at 650 °C at a space velocity (SV) of 2,400 h −1 .…”
Section: Methodsmentioning
confidence: 92%
“…Noble metals, such as Pt, Pd, Ru, and Rh have been recognized as highly active catalysts for ammonia oxidation , . In our previous report , a Co‐Ce‐Zr composite oxide catalyst for the autothermal ammonia cracking was demonstrated. The catalyst was operated at an air‐to‐fuel ratio (AFR) of 0.75 for 1,000 h and showed a stable ammonia conversion of ca.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Moreover, having a hydrogen content of 17.7 wt.%, it is associated with a comparatively high hydrogen ratio. In addition to this, ammonia has a restricted flammability range ratio of nearly 16–25% volumetric in air , . Further, it is comparatively cost‐effective and is a carbon free fuel.…”
Section: Introductionmentioning
confidence: 99%